2018
DOI: 10.1002/ajp.22907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aggressive temperament on endogenous oxytocin levels in adult titi monkeys

Abstract: Coordination of oxytocin (OT) activity and partner interactions is important for the facilitation and maintenance of monogamous pair bonds. We used coppery titi monkeys (Callicebus cupreus) to identify the effects of male aggressive temperament on OT activity, affiliative partner-directed behaviors, aggressive partner-directed behaviors, anxiety-related behaviors, and hormone-behavior interactions. We used a mirror technique, simulating an intruder in the home territory of pairs to elicit behavioral responses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…Studies in humans have also shown an association between increased aggression, competition, and OXT (DeWall et al, 2014; Ne’eman et al, 2016; De Dreu, 2012; Fischer-Shofty et al, 2013). However, studies in monogamous marmosets (Cavanaugh et al, 2018), monogamous titi monkeys (Witczak et al, 2018), female and male rats (De Jong et al, 2014; Calcagnoli et al, 2013; Calcagnoli et al, 2015a; Calcagnoli et al, 2015b), house mice primed for aggressive behavior due to social isolation (Tan et al, 2019), and house mice bred for callous traits (Zoratto et al, 2018) found that OXT was associated with reduced intrasexual competition and aggression. Together with our data, these findings suggest that OXT’s effect on intrasexual aggression may depend heavily on the species, brain areas activated by OXT, and social context.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans have also shown an association between increased aggression, competition, and OXT (DeWall et al, 2014; Ne’eman et al, 2016; De Dreu, 2012; Fischer-Shofty et al, 2013). However, studies in monogamous marmosets (Cavanaugh et al, 2018), monogamous titi monkeys (Witczak et al, 2018), female and male rats (De Jong et al, 2014; Calcagnoli et al, 2013; Calcagnoli et al, 2015a; Calcagnoli et al, 2015b), house mice primed for aggressive behavior due to social isolation (Tan et al, 2019), and house mice bred for callous traits (Zoratto et al, 2018) found that OXT was associated with reduced intrasexual competition and aggression. Together with our data, these findings suggest that OXT’s effect on intrasexual aggression may depend heavily on the species, brain areas activated by OXT, and social context.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, differences in levels of estrogen-receptor α (ERα) expression in the MeA, mPOA, and the VMN are also associated with monogamous behavior and parental care in mandarin voles (Wu et al, 2011). (Aragona et al, 2003;Gingrich et al, 2005), d (López-Gutiérrez et al, 2021, e (Aragona et al, 2006), f (Bales et al, 2007), g (Maninger et al, 2017b), h (Arias Del Razo et al, 2020), i (Hostetler et al, 2017), by D1 receptor antagonist [11C]-SCH2339 binding detection, j (Maninger et al, 2017b), k (Burkett et al, 2011;Resendez et al, 2013Resendez et al, , 2016; l (Lei et al, 2010), m (Lambert et al, 2021), n (Gossman et al, 2021), o (King et al, 2016), p (Ophir et al, 2008b), q (Liu et al, 2001;), r (Pitkow et al, 2001;), s (Witczak et al, 2018), t (Cavanaugh et al, 2014(Cavanaugh et al, , 2018a With respect to OT variants and their impact on behavior, interesting discoveries have been made. Phylogenetic evidence has shown not only OT genetic sequence differences across closely related species, but also a functional cross-talk between AVP and OT, and structural variations in the expressed nonapeptides that could subsequently impact their involvement in neural circuits (French et al, 2016;Pierce et al, 2020).…”
Section: Factors Modulating the Neural Circuitry Of Monogamous Sexual...mentioning
confidence: 99%
“…VTA, ventral tegmental area. a ( Lim and Young, 2004 ), b ( Amadei et al, 2017 ), c ( Aragona et al, 2003 ; Gingrich et al, 2005 ), d ( López-Gutiérrez et al, 2021 ), e ( Aragona et al, 2006 ), f ( Bales et al, 2007 ), g ( Maninger et al, 2017b ), h ( Arias Del Razo et al, 2020 ), i ( Hostetler et al, 2017 ), by D1 receptor antagonist [11C]-SCH2339 binding detection, j ( Maninger et al, 2017b ), k ( Burkett et al, 2011 ; Resendez et al, 2013 , 2016 ); l ( Lei et al, 2010 ), m ( Lambert et al, 2021 ), n ( Gossman et al, 2021 ), o ( King et al, 2016 ), p ( Ophir et al, 2008b ), q ( Liu et al, 2001 ; Lim and Young, 2004 ), r ( Pitkow et al, 2001 ; Lim and Young, 2004 ), s ( Witczak et al, 2018 ), t ( Cavanaugh et al, 2014 , 2018a ), u ( Rothwell et al, 2019 ), v ( Ragen et al, 2015b ), w ( Carp et al, 2019 ), x ( Jarcho et al, 2011 ), y ( Cavanaugh et al, 2018b ), z ( Baxter et al, 2020 )), a+ ( Borie et al, 2022 ), b+ ( Cushing et al, 2003 ), c+ ( Lei et al, 2017 ), d+ ( Jia et al, 2008 ), e+ ( He et al, 2013 ), f+ ( An et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, individual variation in aggression has been shown to predict affiliation within a pair. More characteristically aggressive males (which show higher levels of mate-guarding or "jealous" behavior) tended to be less affiliative with their partners (Witczak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%